Perfil del consumidor de las galerías de artesanía de la comunidad de Tigua - Ortiz Mena, Lisbeth Aracely (2023)
The present investigation seeks to determine the "Consumer profile of the handicraft galleries of the Tigua community", likewise, the question is formulated: What is the consumer profile of handicraft galleries of the Tigua community?, with the objective to build the profile of the "tourist" consumer. This research is justified by theories, theoretical and related models, since the consumer profile was studied, contributing more information for future similar research on the subject. To determine the consumer profile, the quantitative approach methodology, descriptive type of research, non-experimental research design, survey research technique, questionnaire research instrument, and SPSS version 27 was used as a data processing tool.